2015
DOI: 10.1016/j.bbmt.2014.11.482
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pre-Transplant 25-Hydroxy-Vitamin D Levels, Survival and Graft-Versus-Host Disease, in Allogeneic Haematopoietic Stem Cell Transplantation

Abstract: HR: 1.78, 95% CI: 0.98-3.23; P¼0.058) compared with MRD and (HR: 2.30, 95% CI: 1.26-4.21; P¼0.007) with MUD. Conclusions: 1) Among CMV R+ TCD recipients, the incidence of CMV viremia was 79%. 2) In multivariate analysis, CMV D-with decreased risk for CMV viremia compared to D+. 3) Diagnosis of multiple myeloma and allografts from mismatched donor was associated with increased risk. 4) Further studies are needed to assess the effect of CMV donor serostatus in transplant outcomes in TCD. If validated in larger c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The high incidence of vitamin D deficiency in allogeneic HSCT patients, alongside the current controversy (9,11,84,114,115,132,141), emphasizes the need for further studies on the impact of vitamin D deficiency and VDR gene polymorphisms on clinical outcomes to define its role as a biomarker in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The high incidence of vitamin D deficiency in allogeneic HSCT patients, alongside the current controversy (9,11,84,114,115,132,141), emphasizes the need for further studies on the impact of vitamin D deficiency and VDR gene polymorphisms on clinical outcomes to define its role as a biomarker in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, another clinical study showed that cGvHD developed in patients with lower 25(OH)D 3 serum levels at transplantation (9). In contrast, other clinical studies failed to find any correlation between vitamin D serostatus and cGvHD (10,115,132).…”
Section: Graft-versus-host Diseasementioning
confidence: 91%
See 3 more Smart Citations